A method for preparing a ceramic shell for casting
By combining ceramic slurry printing with V-measure casting, combined with negative pressure suction and self-hardening technology, the problem of insufficient accuracy and surface quality of 3D printed ceramic shells is solved, and an efficient and economical method of preparing ceramic shells is achieved.
Patent Information
- Application Number
- CN202410512456.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-26
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-04-26
AI Technical Summary
At this stage, the ceramic shells 3D printed cannot achieve the accuracy and surface finish of traditional cast shells.
By combining ceramic slurry printing with V-measure casting, the casting film is covered on the surface of the pattern and suctioned with negative pressure to closely adhere to the casting film; then printing on the surface of the pattern completed by the coating will have self-hardening. The performance of ceramic slurry is evenly spread and hardened while printing, and finally the ceramic layer is removed from the pattern to form a ceramic shell.
It realizes high-precision and high surface quality model shell manufacturing, with high efficiency, economy and wide applicability, which can significantly improve production efficiency and reduce the single-piece cost of model shells.
Smart Images

Figure CN118418260B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of casting, and in particular to a method for preparing a ceramic shell for casting. Background Art
[0002] In the traditional ceramic shell casting production process, one method is to use the investment casting method to coat the wax mold layer by layer with a slurry mixed with refractory materials and binders (such as water glass, silica sol or ethyl silicate hydrolyzate) to make a ceramic shell. During the process, sanding and other processes are also required to realize the ceramic shell casting of the casting; another method is to use ethyl silicate as a binder to make a ceramic shell through a direct grouting method.
[0003] The process of manufacturing ceramic shells by investment casting has limited its application range due to its complex manufacturing process, long production cycle, high manufacturing cost and high shell scrap rate.
[0004] In the field of single-piece or batch casting production, 3D printing has significant advantages, with high production efficiency, short cycle, simple process, and the ability to freely print complex shells. Therefore, 3D printed ceramic shells are gradually being used in the casting field.
[0005] At this stage, 3D printed ceramic shells are constructed by stacking ceramic powder or slurry layer by layer. The thickness of each layer will affect the surface quality of the final shell. The thinner the printing layer, the smoother the surface, but the printing time will increase. The thicker the printing layer, the higher the production efficiency, but the surface quality will be reduced. In addition, since the ceramic materials used in 3D printing are different from traditional casting shell materials, different materials may exhibit different shrinkage rates during the sintering process, which will also affect the surface accuracy of the printed shell. Although the 3D printed shell can improve the surface quality through post-processing steps such as sanding, polishing and coating, these steps cannot completely eliminate the layered texture generated during the printing process. Therefore, the ceramic shells printed by 3D printing at this stage cannot achieve the accuracy and surface finish of traditional casting shells. Summary of the invention
[0006] In view of this, the present invention proposes a method for preparing a ceramic shell for casting to solve the problem that the ceramic shell printed by 3D printing at this stage cannot achieve the accuracy and surface finish of the traditional casting shell.
[0007] The technical solution of the present invention is achieved in this way:
[0008] The present invention provides a method for preparing a ceramic shell for casting, the preparation method comprising the following steps:
[0009] S1, prepare the pattern for modeling;
[0010] S2, covering the casting film on the pattern, and closely attaching the casting film to the surface of the pattern by negative pressure suction;
[0011] S3, printing is performed on the surface of the coated pattern, and the ceramic slurry with self-hardening properties is evenly spread on the pattern, and hardened while printing;
[0012] S4. When the ceramic slurry tightly covers the surface of the mold and completely hardens into a ceramic layer, the ceramic layer is removed from the mold to obtain a ceramic shell.
[0013] On the basis of the above technical solution, preferably, before printing on the surface of the pattern, a sand box is placed on the coated pattern, so that the printing of the ceramic slurry is completed in the sand box.
[0014] On the basis of the above technical solution, preferably, in step S3, the ceramic slurry is dehydrated by passing warm air or vacuum into the sand box, so that the ceramic layer is hardened quickly.
[0015] On the basis of the above technical scheme, preferably, the self-hardening ceramic slurry contains the following components in a ratio by weight percentage: 10-20% binder, 60-70% refractory material, 5-10% filler, 1-3% promoter, 0.1-0.5% anti-cracking agent, 0.5-1% wetting agent, 0.1-0.5% defoaming agent, and the rest is water.
[0016] Further, preferably, the binder is silica sol or water glass having a silica modulus of 20-40, the refractory material is one or more of silica sand, corundum sand, and bauxite sand having a particle size range of 100-270 mesh, the filling material is alumina powder or titanium oxide powder having a particle size less than 10 microns, the promoter is sodium carbonate or calcium carbonate for accelerating the hardening speed of the silica sol, the anti-cracking agent is polypropylene fiber or lignin fiber for improving the anti-cracking performance of the shell, the wetting agent is polyethylene glycol or fatty alcohol polyoxyethylene ether for improving the wettability of the slurry, and the defoaming agent is silicone oil for reducing the generation of bubbles in the slurry.
[0017] Furthermore, preferably, the preparation steps of the self-hardening ceramic slurry include:
[0018] Step 1: Add the required weight ratio of refractory material and filler material into the mixer and stir evenly;
[0019] Step 2: Add a predetermined proportion of anti-cracking agent to the mixed refractory material and filler material, and continue stirring to evenly distribute the fibers;
[0020] Step 3: prepare two solutions, one is a accelerator solution and the other is a binder solution, and then pour the two solutions into a mixer containing refractory material, filler material and anti-cracking agent at the same time;
[0021] Step 4: During the mixing process, slowly add the wetting agent and defoaming agent while stirring until they are completely mixed to form a homogeneous ceramic slurry.
[0022] On the basis of the above technical solution, preferably, step S4 further includes the following steps:
[0023] Step S41, after the ceramic layer is completely hardened, the ceramic layer is retained on the surface of the mold without being removed, and molding sand is placed on the surface of the ceramic layer so that the molding sand fills the entire sand box;
[0024] Step S42, covering the top surface of the sand box with a casting film, and then evacuating the sand box, while releasing the negative pressure suction operation on the casting film on the surface of the pattern, after the sand box forms a certain vacuum degree, taking the sand box out of the pattern to form a casting mold.
[0025] Preferably, the molding sand is dry sand or resin sand or water glass sand with a self-hardening binder.
[0026] Preferably, the vacuum degree of the vacuum treatment is 30-70 KPa.
[0027] Preferably, the casting film is selected from one or more of a polyethylene film, an ethylene-vinyl acetate copolymer film and a polyvinyl alcohol film.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The method for preparing a ceramic shell for casting disclosed in the present invention realizes the manufacture of a shell with high precision and high surface quality by combining ceramic slurry printing with V-method casting, and has high efficiency, economy and wide applicability.
[0030] (2) In the production of small and medium-sized castings, the ceramic shell disclosed in this embodiment can significantly improve production efficiency due to the high efficiency of its preparation method. Compared with traditional V-method casting, this ceramic shell can be prepared quickly, and due to its optimized structure, it can be used multiple times without damaging the shell performance, reducing the casting production cycle affected by the time required for shell preparation. At the same time, the characteristic of multiple use directly reduces the unit cost of the shell.
[0031] (3) Printing the ceramic slurry in the sand box can effectively limit the final size and shape of the shell. Since the boundary of the sand box provides a physical limit for the ceramic slurry, this is particularly important for maintaining the consistency and repeatability of the shell, especially when mass-producing small and medium-sized casting shells. At the same time, limiting the printing process to the sand box can effectively prevent the overflow of the ceramic slurry when it is applied to the surface of the mold. This not only helps to keep the work area clean, but also ensures the effective use of the slurry and avoids slurry waste.
[0032] (4) The evaporation of water in the ceramic slurry can be significantly accelerated by introducing warm air or applying vacuum, thereby accelerating the hardening process of the slurry. This can shorten the preparation time of the shell and improve production efficiency. The rapid dehydration and hardening process helps to reduce cracks or deformation that may occur in the shell during the drying process because it can reduce the stress inside the material during the drying process. Therefore, this method not only accelerates the preparation process, but also improves the final quality of the shell.
[0033] (5) Through the ceramic slurry preparation steps provided by the present invention, a ceramic slurry with self-hardening properties can be prepared, which can quickly harden under natural conditions without sintering, thereby simplifying the preparation process of the ceramic shell, reducing energy consumption, and improving production efficiency. In addition, by accurately controlling the proportion of various components and the preparation process, it can be ensured that the shell has good refractory, crack resistance and surface quality, meeting the needs of high-quality casting.
[0034] (6) By using molding sand as an auxiliary material, the excellent properties of the ceramic shell are maintained, and the strength and thickness of the ceramic shell are improved by combining vacuum technology, solving the challenges faced by traditional methods in preparing large casting shells. In addition, this method can also shorten the preparation time and improve production efficiency to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 It is a schematic diagram of the vacuum state of the casting film disclosed in the present invention on the pattern;
[0037] Figure 2 It is a schematic diagram of the state of printing the self-hardening ceramic slurry on the pattern disclosed in the present invention;
[0038] Figure 3It is a schematic diagram of the state of the ceramic layer disclosed in the present invention after hardening;
[0039] Figure 4 It is a schematic diagram of the state of filling molding sand on the surface of the ceramic mold shell disclosed in the present invention;
[0040] Figure 5 It is a schematic diagram of the state of vacuum suction of the sand box disclosed in the present invention;
[0041] Figure 6 It is a schematic diagram of the state where the shape and pattern disclosed in the present invention are separated;
[0042] Reference numerals:
[0043] 1. Pattern; 2. Casting film; 3. Self-hardening ceramic slurry; 4. Sand box; 5. Molding sand; 6. Modeling; S. Ceramic shell. DETAILED DESCRIPTION
[0044] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] like Figure 1 As shown, combined Figure 2-3 The present invention provides a method for preparing a ceramic shell for casting, comprising the following steps:
[0046] S1. Prepare a mold for molding. Specifically, the mold disclosed in this embodiment is a model used in a V-method casting process, and the mold is used as a basis for the subsequent preparation of a ceramic shell. In this embodiment, the mold can be made of wood, plastic, metal or resin materials, and the surface of the mold can be processed by CNC to form a shape that fits the outer surface of the casting. The surface of the mold needs to maintain a certain degree of smoothness, thereby ensuring the final surface accuracy of the ceramic shell, thereby ensuring that the shape and surface quality of the final casting meet the requirements.
[0047] S2. Cover the casting film on the pattern and attach the casting film tightly to the surface of the pattern through negative pressure suction. Specifically, multiple suction holes are evenly distributed on the surface of the pattern. The pattern can be connected to a negative pressure suction system to ensure that the casting film fits tightly to the surface of the pattern by vacuuming when the casting film is covered on the surface of the pattern. The tightly fitted casting film can effectively replicate the details of the pattern and provide a smooth and accurate bottom layer for the ceramic slurry. This not only reduces casting defects, but also improves the surface quality of the shell and the final casting.
[0048] S3. Printing is performed on the surface of the coated pattern, and the ceramic slurry with self-hardening properties is evenly spread on the pattern, and hardened while printing.
[0049] The printing of this step can be understood as applying the self-hardening ceramic slurry evenly on the surface of the coated model through a specific process, such as spraying, coating, etc., and allowing it to gradually harden during the coating process. By controlling the coating thickness and hardening rate of the slurry, the required shell thickness and shape can be accurately formed. The use of self-hardening slurry simplifies the production process of penetrating 3D printed ceramic shells, avoids the problem of ceramic shell cracks during the traditional heat treatment hardening process, ensures the surface quality of the ceramic shell, and speeds up the production cycle.
[0050] S4. When the ceramic slurry tightly covers the surface of the mold and completely hardens into a ceramic layer, the ceramic layer is removed from the mold to obtain a ceramic shell.
[0051] After the ceramic slurry is completely hardened, a solid ceramic layer is formed. At this time, it is separated from the pattern to obtain the final ceramic shell. The finished ceramic shell will completely replicate all the details of the pattern surface, maintaining high precision and high surface quality. In addition, the hardened ceramic layer has good mechanical strength and temperature resistance, meeting the requirements of the casting process.
[0052] At the same time, it is worth noting that in the production of small and medium-sized castings, the ceramic shell disclosed in this embodiment can significantly improve production efficiency due to the high efficiency of its preparation method. Compared with traditional V-method casting, this ceramic shell can be prepared quickly, and due to its optimized structure, it can be used multiple times without damaging the shell performance, reducing the casting production cycle affected by the time required for shell preparation. At the same time, the characteristic of multiple use directly reduces the unit cost of the shell.
[0053] The ceramic shell preparation method disclosed in this embodiment can ensure high precision and good surface quality of the shell, which is crucial to improving the quality of the final casting. Since the ceramic shell can be used multiple times, the generation of waste materials is relatively reduced, and the impact on the environment is also reduced accordingly. In addition, compared with the disposable materials that may be used in traditional V-method casting, this method is more environmentally friendly.
[0054] In summary, the method for preparing a ceramic shell for casting disclosed in the present invention realizes the manufacturing of a shell with high precision and high surface quality by combining ceramic slurry printing with V-method casting, and has high efficiency, economy and wide applicability.
[0055] Since the ceramic slurry has a certain fluidity, in order to prevent the ceramic slurry from overflowing from the pattern to the outside during the process of printing the ceramic slurry on the pattern, this embodiment further provides some steps. Figure 2 and 3As shown, before printing on the surface of the pattern, a sand box is placed on the coated pattern so that the printing of the ceramic slurry is completed in the sand box.
[0056] With the above technical solution, printing the ceramic slurry in the sand box can effectively limit the final size and shape of the shell, because the boundary of the sand box provides a physical limit for the ceramic slurry. This is particularly important for maintaining the consistency and repeatability of the shell, especially when mass-producing small and medium-sized casting shells. At the same time, limiting the printing process to the sand box can effectively prevent the overflow of the ceramic slurry when it is applied to the surface of the pattern. This not only helps to keep the work area clean, but also ensures the effective use of the slurry and avoids the waste of slurry.
[0057] As some preferred embodiments, during step S3, the ceramic slurry is dehydrated by passing warm air or vacuum into the sand box, so that the ceramic layer is quickly hardened.
[0058] By introducing warm air or applying vacuum, the evaporation of water in the ceramic slurry can be significantly accelerated, thereby speeding up the hardening process of the slurry, thereby shortening the preparation time of the shell and improving production efficiency.
[0059] In addition, the rapid dehydration and hardening process helps to reduce the possibility of cracks or deformation of the shell during the drying process, because it can reduce the stress inside the material during the drying process. Therefore, this method not only speeds up the preparation process, but also improves the final quality of the shell.
[0060] In the traditional ceramic shell 3D printing process, the slurry is stacked layer by layer and sintered. The slurry printing process requires high-temperature sintering, which will affect the quality of the inner surface of the shell. The present invention directly prints the ceramic slurry on the surface of the mold. In order to eliminate high-temperature sintering, this embodiment adopts a method of hardening the ceramic slurry while printing. In order to achieve self-hardening of the ceramic slurry, this embodiment discloses a component of the ceramic slurry.
[0061] Specifically, the self-hardening ceramic slurry of this embodiment contains the following components in a ratio by weight percentage: 10-20% binder, 60-70% refractory material, 5-10% filler, 1-3% promoter, 0.1-0.5% anti-cracking agent, 0.5-1% wetting agent, 0.1-0.5% defoaming agent, and the rest is water.
[0062] Among them, the binder is used to provide the adhesion of the slurry, ensure the bonding of the refractory material and the filling material, and the proportion of the binder directly affects the consistency of the slurry and the structural strength of the final shell. The refractory material constitutes the main body of the slurry, provides high temperature resistance, and ensures that the shell will not melt or deform during high temperature casting. The filling material is used to increase the volume of the slurry, improve the overall strength of the shell, improve the mechanical properties of the shell, and reduce damage during the casting process. The accelerator is used to accelerate the hardening process of the slurry, so that the slurry can reach the required hardness in a shorter time and speed up production. The anti-cracking agent is used to improve the stability of the slurry during the drying process, prevent the generation of cracks, improve the quality of the shell, and reduce defects caused by improper drying. The wetting agent is used to improve the fluidity and coating performance of the slurry, making it easier to coat evenly, ensuring the smoothness and uniformity of the shell surface, and improving the surface quality of the casting. The defoaming agent is used to reduce the generation of bubbles during the mixing and coating of the slurry, avoid the presence of pores in the shell, and improve the density of the shell and the integrity of the casting.
[0063] Specifically, the binder disclosed in this embodiment is silica sol, which has good adhesion and high temperature resistance, and its silica modulus is 20-40, which indicates the ratio of silicon to oxygen in silica sol, affecting its bonding strength and fire resistance. As some other embodiments, the binder can also be water glass.
[0064] The refractory material is silica sand, which has good heat resistance and thermal stability. Its particle size range is 100-270 mesh, which affects the fluidity of the slurry and the surface smoothness of the shell. As some other embodiments, the refractory material can also be corundum sand or bauxite sand. In addition, the refractory material can also be one or more of silica sand, corundum sand, and bauxite sand.
[0065] The filling material is aluminum oxide powder, which improves the wear resistance and mechanical strength of the shell, and its particle size is less than 10 microns, which helps to improve the density and fineness of the shell. As some other embodiments, the filling material can also be titanium oxide powder.
[0066] The accelerator is sodium carbonate or calcium carbonate, which is used to accelerate the hardening speed of silica sol and shorten the curing time of the slurry.
[0067] The anti-cracking agent is polypropylene fiber or lignin fiber, which is used to improve the anti-cracking performance of the shell and reduce the generation of cracks during the drying process.
[0068] The wetting agent is polyethylene glycol or fatty alcohol polyoxyethylene ether, which is used to improve the wettability of the slurry. The defoaming agent is silicone oil, which is used to reduce the generation of bubbles in the slurry and improve the density of the shell.
[0069] Embodiment 1
[0070] The self-hardening ceramic slurry is composed of the following components in a weight percentage ratio: 10% silica sol, 70% silica sand, 5% alumina powder, 1% sodium carbonate, 0.1% polypropylene fiber, 0.5% polyethylene glycol, 0.1% silicone oil, and the rest is water.
[0071] The method for preparing a self-hardening ceramic slurry comprises the following steps:
[0072] Step 1: Add 70% silica sand and 5% alumina powder into the mixer and stir evenly; this step ensures that the refractory material and the filling material are evenly mixed, laying the foundation for the preparation of high-quality ceramic slurry.
[0073] Step 2: Add 0.1% polypropylene fiber to the mixed silica sand and alumina powder, and continue stirring to evenly distribute the fiber; the evenly distributed fiber in this step can improve the crack resistance of the shell and reduce cracks during the drying process.
[0074] Step 3: prepare two solutions respectively, one is an aqueous solution containing 1% sodium carbonate, and the other is a 10% silica sol aqueous solution, and then pour the two solutions into a mixer containing refractory materials, fillers and anti-cracking agents at the same time; this step mixes the sodium carbonate aqueous solution with the silica sol, and then adds them to the refractory materials and anti-cracking agents to ensure that the binder and promoter are evenly distributed.
[0075] Step 4: During the mixing process, slowly add 0.5% polyethylene glycol and 0.1% silicone oil, stirring while adding until they are completely mixed to form a homogeneous ceramic slurry, ensuring that the slurry has good uniformity and coating performance.
[0076] Embodiment 2
[0077] The self-hardening ceramic slurry is composed of the following components in a weight percentage ratio: 20% silica sol, 60% corundum sand, 10% titanium oxide powder, 3% sodium carbonate, 0.5% lignin fiber, 1% polyethylene glycol, 0.5% silicone oil, and the rest is water.
[0078] The steps of the method for preparing the self-hardening ceramic slurry disclosed in Example 2 are as follows:
[0079] Step 1: Add 60% corundum sand and 10% titanium oxide powder into a mixer and stir evenly.
[0080] Step 2: Add 0.5% lignin fiber to the mixed corundum sand and titanium oxide powder, and continue stirring to evenly distribute the fiber.
[0081] Step 3: prepare two solutions respectively, one is an aqueous solution containing 3% sodium carbonate, and the other is a 20% silica sol aqueous solution, and then pour the two solutions into a mixer containing refractory materials and anti-cracking agents at the same time.
[0082] Step 4: During the mixing process, slowly add 1% polyethylene glycol and 0.5% silicone oil while stirring until they are completely mixed to form a homogeneous ceramic slurry.
[0083] Embodiment 3
[0084] The self-hardening ceramic slurry is composed of the following components in a weight percentage ratio: 15% silica sol, 65% silica sand, 7.5% alumina powder, 2% sodium carbonate, 0.3% polypropylene fiber, 0.75% polyethylene glycol and 0.3% silicone oil, and the rest is water.
[0085] The steps of the method for preparing the self-hardening ceramic slurry disclosed in Example 3 are as follows:
[0086] Step 1: Add 65% silica sand and 7.5% alumina powder into a mixer and stir evenly.
[0087] Step 2: Add 0.3% polypropylene fiber to the mixed silica sand and alumina powder and continue stirring to evenly distribute the fiber.
[0088] Step 3: prepare two solutions respectively, one is an aqueous solution containing 2% sodium carbonate, and the other is 15% silica sol, and then pour these two solutions into a mixer containing refractory materials and anti-cracking agents at the same time.
[0089] Step 4: During the mixing process, slowly add 0.75% polyethylene glycol and 0.3% silicone oil while stirring until they are completely mixed to form a homogeneous ceramic slurry.
[0090] Through the ceramic slurry preparation steps provided by the present invention, a ceramic slurry with self-hardening properties can be prepared, and the slurry can be quickly hardened under natural conditions without sintering, thereby simplifying the preparation process of the ceramic shell, reducing energy consumption, and improving production efficiency. In addition, by accurately controlling the proportion of various components and the preparation process, it can be ensured that the shell has good refractory, crack resistance and surface quality, meeting the needs of high-quality casting.
[0091] The ceramic shell prepared by the method for preparing a ceramic shell for casting disclosed in the present invention is prepared by directly printing ceramic slurry on the surface of a pattern designed by a V-method process, and allowing the ceramic slurry to self-harden to form a solid ceramic layer. The ceramic layer is separated from the pattern to obtain a final ceramic shell. This ceramic shell is not thick and can be suitable for small and medium-sized castings.
[0092] When large castings are required, the thickness of the ceramic shell cannot be met. If the thickness of the ceramic shell is increased, multiple ceramic layers need to be printed on the pattern to increase the number of ceramic layers. Since the self-hardening of the ceramic slurry also takes a certain amount of time, the increase in the number of ceramic layers will be accompanied by an increase in the hardening time, which will reduce the preparation time of the ceramic shell as a whole.
[0093] To this end, this embodiment further proposes some operation steps based on step S4. Figure 4-6 As shown, a shell mold capable of forming large castings is obtained.
[0094] Specifically, in step S41, after the ceramic layer is completely hardened, the ceramic layer is retained on the surface of the mold without being removed, and molding sand is placed on the surface of the ceramic layer so that the molding sand fills the entire sand box;
[0095] This step utilizes the molding sand to provide additional support and wrapping, laying the foundation for the subsequent increase in the thickness of the shell. By placing the molding sand directly on the hardened ceramic layer, the overall strength and thickness of the shell can be increased without directly increasing the ceramic layer itself, while also providing physical support for increasing the number of ceramic layers.
[0096] Step S42, covering the top surface of the sand box with a casting film, and then evacuating the sand box, while releasing the negative pressure suction operation on the casting film on the surface of the pattern, after the sand box forms a certain vacuum degree, taking the sand box out of the pattern to form a casting mold.
[0097] In this step, vacuuming is used to ensure a close bond between the molding sand and the ceramic layer, while negative pressure is also used to make the molding sand more solid, forming an additional support layer. The vacuuming process not only enhances the compactness of the molding sand and the overall structural strength of the mold shell, but also helps to increase the thickness and strength of the mold shell by forming a certain vacuum degree without increasing the hardening time of the ceramic layer itself, thereby meeting the needs of large castings.
[0098] The above method effectively utilizes molding sand as an auxiliary material, which not only maintains the excellent performance of the ceramic shell, but also improves the strength and thickness of the shell by combining vacuum technology, solving the challenges faced by traditional methods in preparing large casting shells. In addition, this method can also shorten the preparation time and improve production efficiency to a certain extent.
[0099] Preferably, the molding sand is dry sand or resin sand or water glass sand with a self-hardening binder.
[0100] Among them, dry sand is easy to handle and shape, and can provide a certain support for covering the ceramic layer. Since it does not contain a binder, the fluidity of dry sand is better in the subsequent vacuuming process, which is conducive to forming a compact sand layer.
[0101] After adding self-hardening binder, resin sand will harden under certain conditions (such as exposure to moisture in the air) to form a stronger structure. This is very beneficial for enhancing the overall strength and stability of the ceramic shell, especially when making large casting shells.
[0102] Water glass sand is a kind of molding sand with good bonding properties, which can harden quickly after adding hardener. Its use can improve the structural integrity and load-bearing capacity of the shell, especially when preparing large or complex shaped casting shells.
[0103] In this embodiment, the vacuum degree of the vacuum treatment is 30-70Kpa. Through vacuuming, the molding sand can be more closely attached to the ceramic layer, reducing the gap, thereby improving the density and strength of the mold shell. The appropriate vacuum degree helps to enhance the adhesion between the mold shell surface and the molding sand, ensure that the molding sand does not fall off during the casting process, and improve the surface quality of the casting.
[0104] Casting film plays a vital role in the casting process. It is necessary to ensure that the selected material can withstand the high temperature in the casting process, has sufficient strength and elasticity, and also needs to prevent rupture during vacuuming and sand injection. The casting film is selected from one or more of polyethylene film, ethylene-vinyl acetate copolymer film and polyvinyl alcohol film. In the actual casting production process, the film material with corresponding performance can be selected according to the precision and surface quality requirements of the casting.
[0105] It is worth noting that the casting mold made of molding sand as an auxiliary material needs to be connected to a negative pressure suction system during use. This operation is similar to the V-method casting process. A large casting requires two upper and lower molds. Both molds are supported by ceramic mold shells and vacuumed molding sand. Since the ceramic mold shell replicates the surface shape of the pattern, the inner surface of the ceramic mold shell has a higher surface accuracy. Therefore, when large castings are formed, it can meet the quality requirements of the casting surface. In addition, since the ceramic mold shell is supported by molding sand, the entire mold can be used multiple times. Compared with the disposable materials that may be used in traditional V-method casting, this method is more environmentally friendly, lower cost and more efficient.
[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a ceramic shell for casting, characterized in that: The preparation method comprises the following steps: S1. Prepare a mold for molding, and shape the mold surface by CNC machining to fit the outer surface of the casting; S2, covering the casting film on the pattern, evenly distributing a plurality of suction holes on the surface of the pattern, and closely attaching the casting film to the surface of the pattern by negative pressure suction; S3, printing is performed on the surface of the coated pattern, and the ceramic slurry with self-hardening properties is evenly spread on the pattern, and hardened while printing; S4. When the ceramic slurry tightly covers the surface of the mold and completely hardens into a ceramic layer, the ceramic layer is removed from the mold to obtain a ceramic shell; Before printing on the surface of the pattern, a sand box is placed on the coated pattern so that the printing of the ceramic slurry is completed in the sand box; Step S4 also includes the following steps: Step S41, after the ceramic layer is completely hardened, the ceramic layer is retained on the surface of the mold without being removed, and molding sand is placed on the surface of the ceramic layer so that the molding sand fills the entire sand box; Step S42, covering the top surface of the sand box with a casting film, and then vacuumizing the sand box, while releasing the casting film on the surface of the pattern to perform a negative pressure suction operation, and after the sand box forms a certain vacuum degree, taking the sand box out of the pattern to form a casting mold; The self-hardening ceramic slurry comprises the following components in weight percentage: 10-20% binder, 60-70% refractory material, 5-10% filler material, 1-3% promoter, 0.1-0.5% anti-cracking agent, 0.5-1% wetting agent, 0.1-0.5% defoaming agent, and the rest is water; The binder is silica sol or water glass, and its silica modulus is 20-40; the refractory material is one or more of silica sand, corundum sand, and bauxite sand, and its particle size range is 100-270 mesh; the filler material is alumina powder or titanium oxide powder, and its particle size is less than 10 microns; the promoter is sodium carbonate or calcium carbonate, which is used to accelerate the hardening speed of silica sol; the anti-cracking agent is polypropylene fiber or lignin fiber, which is used to improve the anti-cracking performance of the shell; the wetting agent is polyethylene glycol or fatty alcohol polyoxyethylene ether, which is used to improve the wettability of the slurry; the defoaming agent is silicone oil, which is used to reduce the generation of bubbles in the slurry; The preparation steps of the self-hardening ceramic slurry include: Step 1: Add the required weight ratio of refractory material and filler material into the mixer and stir evenly; Step 2: Add a predetermined proportion of anti-cracking agent to the mixed refractory material and filler material, and continue stirring to evenly distribute the fibers; Step 3: prepare two solutions, one is a accelerator solution and the other is a binder solution, and then pour the two solutions into a mixer containing refractory material, filler material and anti-cracking agent at the same time; Step 4: During the mixing process, slowly add the wetting agent and defoaming agent while stirring until they are completely mixed to form a homogeneous ceramic slurry.
2. The method for preparing a ceramic shell for casting according to claim 1, characterized in that: During step S3, the ceramic slurry is dehydrated by passing warm air or vacuum into the sand box, so that the ceramic layer is quickly hardened.
3. The method for preparing a ceramic shell for casting according to claim 1, characterized in that: The molding sand is dry sand or resin sand or water glass sand with a self-hardening binder.
4. The method for preparing a ceramic shell for casting according to claim 1, characterized in that: The vacuum degree of the vacuum treatment is 30-70Kpa.
5. The method for preparing a ceramic shell for casting according to claim 1, characterized in that: The casting film is selected from one or more of a polyethylene film, an ethylene-vinyl acetate copolymer film and a polyvinyl alcohol film.
Citation Information
Patent Citations
Ceramic type precise casting method
CN103170578A
3D printing sand core cast aluminum water-based paint and preparation method thereof
CN116652103A
Technology for precision casting metal die and parts
CN1385265A